The acute management of trauma hemorrhage: a systematic review of randomized controlled trials. - Curry, N; Hopewell, S; Dorée, C; Hyde, C; Brohi, K; Stanworth, S (2011)
INTRODUCTION: Worldwide, trauma is a leading cause of death and disability. Haemorrhage is responsible for up to 40% of trauma deaths. Recent strategies to improve mortality rates have focused on optimal methods of early hemorrhage control and correction of coagulopathy. We undertook a systematic review of randomized controlled trials (RCT) which evaluated trauma patients with hemorrhagic shock within the first 24 hours of injury and appraised how the interventions affected three outcomes: bleeding and/or transfusion requirements; correction of trauma induced coagulopathy and mortality. METHODS: Comprehensive searches were performed of MEDLINE, EMBASE, CENTRAL (The Cochrane Library Issue 7, 2010), Current Controlled Trials, ClinicalTrials.gov, the World Health Organization International Clinical Trials Registry Platform (ICTRP) and the National Health Service Blood and Transplant Systematic Review Initiative (NHSBT SRI) RCT Handsearch Database. RESULTS: A total of 35 RCTs were identified which evaluated a wide range of clinical interventions in trauma hemorrhage. Many of the included studies were of low methodological quality and participant numbers were small. Bleeding outcomes were reported in 32 studies; 7 reported significantly reduced transfusion use following a variety of clinical interventions, but this was not accompanied by improved survival. Minimal information was found on traumatic coagulopathy across the identified RCTs. Overall survival was improved in only three RCTs: two small studies and a large study evaluating the use of tranexamic acid. CONCLUSIONS: Despite 35 RCTs there has been little improvement in outcomes over the last few decades. No clear correlation has been demonstrated between transfusion requirements and mortality. The global trauma community should consider a coordinated and strategic approach to conduct well designed studies with pragmatic endpoints.